A Caging Inspired Gripper using Flexible Fingers and a Movable Palm - Beddow, Luke; Wurdemann, Helge; Kanoulas, Dimitrios (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2021)
This paper proposes the design of a robotic gripper motivated by the bin-picking problem, where a variety of objects need to be picked from cluttered bins. The presented gripper design focuses on an enveloping cage-like approach, which surrounds the object with three hooked fingers, and then presses into the object with a movable palm. The fingers are flexible and imbue grasps with some elasticity, helping to conform to objects and, crucially, adding friction to cases where an object cannot be caged. This approach proved effective on a set of basic shapes, such as cuboids and cylinders, in which every object could be grasped. In particular, flat bottom parts could be grasped in a very stable manner, as demonstrated by testing grasps with multiple 5N and 10N disturbances. A set of supermarket items were also tested, highlighting promising features such as effective grasping of fruits and vegetables, as well as some limitations in the current embodiment, which is not always able to slip the fingers underneath objects.